William Henry Harrison papers - Harrison, William Henry, 1773-1841.; Cleaves, Freeman, 1904-
Correspondence and military papers, chiefly for the period 1796-1841, with special emphasis on Indian campaigns and affairs; letterbook (1812-1813) reporting on the War of 1812 in the Northwest Territory; and correspondence regarding Harrison's unsuccessful campaign for the presidency in 1836. Includes a few posthumous family papers and letters and a chronology of Harrison's life by his biographer, Freeman Cleaves. Correspondents include John Armstrong, William Eustis, Duff Green, John Johnston, Joel Leftwich, Duncan McArthur, Return Jonathan Meigs, James Monroe, John C. Payne, William C. Schenck, Isaac Shelby, Edward Tupper, James Wilkinson, James Winchester, and John Wingate.
Available on microfilm, in part
U. S. president, senator, representative, and army officer from Ohio.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index published by the Library of Congress in 1960 available in the Library of Congress Manuscript Reading Room and on Internet. Cataloged in record 60060012.
Keywords: Armstrong, John, -- 1758-1843 -- Correspondence; Eustis, William, -- 1753-1825 -- Correspondence; Green, Duff, -- 1791-1875 -- Correspondence; Johnston, John, -- 1775-1861 -- Correspondence; Leftwich, Joel, -- 1759-1846 -- Correspondence; McArthur, Duncan, -- 1772-1839 -- Correspondence; Meigs, Return Jonathan, -- 1764-1825 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Payne, John C. -- Correspondence; Schenck, William Cortenus, -- 1773-1821 -- Correspondence; Shelby, Isaac, -- 1750-1826 -- Correspondence; Tupper, Edward White, -- 1771-1823 -- Correspondence; Wilkinson, James, -- 1757-1825 -- Correspondence; Winchester, James, -- 1752-1826 -- Correspondence; Harrison family; Indians of North America -- Government relations; Indians of North America -- Wars; Presidents -- United States -- Election -- 1836.; Northwest, Old -- History -- War of 1812.; United States -- History -- War of 1812.; Army officers; Presidents -- United States; Representatives, U.S. Congress -- Ohio; Senators, U.S. Congress -- Ohio